Words from of “house of captivity”. Lexis from the Soviet forced-labour camp and from exile in the memoir of Beata Obertyńska - Pacuła, Jarosław (Papers in Linguistics, 2019)
The article concerns one of the little-known areas of linguistic research – the influence of the Russian language on the Polish language and the functioning of the Polish language in environments of extreme situations of imprisonment. The material for this study is based on a collection of about thirty dictionary units based on excerpts from the memories of ex-prisoners and from the memories of Beata Obertyńska (she belonged to the poetic group “Skamander”). This report, to varying levels, is filled with characteristic vocabulary related to the realities described by the author. In the article, the author discussed lexemes belonging to the language used in Soviet forced-labour camps. The vocabulary was presented as linguistic evidence. Historical comments accompany deliberations.